2020
DOI: 10.1523/jneurosci.0610-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

µ Opioid Receptor Agonism for L-DOPA-Induced Dyskinesia in Parkinson's Disease

Abstract: Parkinson's disease (PD) is characterized by severe locomotor deficits and is commonly treated with the dopamine precursor L-DOPA, but its prolonged usage causes dyskinesias referred to as L-DOPA-induced dyskinesia (LID). Several studies in animal models of PD have suggested that dyskinesias are associated with a heightened opioid cotransmitter tone, observations that have led to the notion of a LID-related hyperactive opioid transmission that should be corrected by m opioid receptor antagonists. Reports that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…This is perhaps due to action at multiple sites that includes DOR activity. Consistent with the lack of effect of pure MOR antagonists, is the study of ADC-02265510, a MOR agonist which has shown anti-dyskinetic activity [9]. It is further interesting that sub-anesthetic ketamine treatment has recently been shown to be anti-dyskinetic and anti-Parkinsonian in rodent models [48,49].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is perhaps due to action at multiple sites that includes DOR activity. Consistent with the lack of effect of pure MOR antagonists, is the study of ADC-02265510, a MOR agonist which has shown anti-dyskinetic activity [9]. It is further interesting that sub-anesthetic ketamine treatment has recently been shown to be anti-dyskinetic and anti-Parkinsonian in rodent models [48,49].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the mixed KOR agonist/MOR antagonist nalbuphine was shown to reduce LID in dyskinetic non-human LID primates [45]. Blockade of the MOR receptor alone, with two highly-selective MOR antagonists, ADC-02520849 and CTAP, did not reduce LID [9,46], while a MOR antagonist with a very low selectivity, ADL5510, was successful in reducing LID [47]. This is perhaps due to action at multiple sites that includes DOR activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant results of this experiment may be due to the dualistic nature of the treatment strategy used -highly selective μ-opioid receptor antagonism did not improve dyskinesia in the tested 6-OHDA rats [135]. Only μ receptor agonists appeared to reduce the incidence of LID when used alone [136].…”
Section: Opioid Modulatorsmentioning
confidence: 87%
“…The direction of effect in our data (Supplementary Table S2 ) suggests that carriers of the G allele have shorter time-to-LID onset, and that therefore differential sensitivity of the mu opioid receptor to endogenous opioids could play a role in time-to-LID onset. By extension, agonists of the mu opioid receptor might be therapeutic in slowing LID onset, and can provide anti-dyskinetic benefit as has been recently discussed 13 .…”
Section: Discussionmentioning
confidence: 98%